The Factors Related to The Utilization of Antenatal Care Services in Oesapa Community Health Center - Joece Paulin Rambu Loda; Masrida Sinaga; Rina Waty Sirait (Lontar : Journal of Community Health, 2022)
Efforts to prevent maternal death are carried out by utilizing ANC services to keep the condition of the mother and fetus healthy and to detect earlier the high risks and abnormalities during pregnancy. In 2020 the number of pregnant women increased but there was a decrease in ANC visits by 9.7% K1 and by 8.5% K4 at Puskesmas Oesapa. The decreasing coverage of antenatal care shows the low utilization of ANC services by pregnant women. The purpose of this study was to determine the facts related to using ANC services at Puskesmas Oesapa. This type of research is quantitative with a cross-sectional study design. This research was conducted at the Puskesmas Oesapa, with a sample of 80 mothers who gave birth in 2021, and used a purposive sampling technique. Data was collected using an interview with a questionnaire. The data analysis used was univariate and bivariate with a chi-square statistical test. The results showed that the variables that had a relationship with the use of ANC services were occupation (95% CI 0,004 = to 0,007;ρ-value = 0.006), family support (95% CI = 0,002 to 0,004; ρ-value = 0.003), a distance of residence (95% CI = 0,008 to 0,011; ρ-value = 0.011). Meanwhile, the mother's condition variable (95% CI = 0,435 to 0,455; ρ-value= 0.471) has no relationship to the use of ANC services at Puskesmas Oesapa. It is expected that mothers check their pregnancies regularly to detect early complications in pregnancy and that health workers can improve health promotion related to the utilization of ANC.